Acceptance and Commitment Therapy for enclosed spaces phobia: A randomized clinical trial (Brazilian Journal of Behavioral and Cognitive Therapy, 2017)
Several medical procedures, especially magnetic resonance imaging (MRI), can be severely distressing for individuals who suffer from enclosed space phobia. The psychotherapeutic approach to minimize the discomfort for these patients can be a safe and effective alternative to increase these patients' acceptance of the exam. A cohort of 30 subjects with MRI aversion was randomly divided into 2 intervention groups: 15 subjects received 1 session of Acceptance and Commitment Therapy (ACT) based psychotherapy, and 15 subjects received 7 sessions ACT based psychotherapy. The primary outcome was considered being able to undergo an MRI simulation after therapy completion. Subjects also filled a set of questionnaires at baseline and after 1 month and 3 months of treatment completion. The self-assessment questionnaires were performed before and after the treatment: Rachmann and Taylor Claustrophobia Inventory (1993), Beck Depression Inventory (1961) and the State-Trait Anxiety Inventory (STAI) (1970). Subjects who received the seven session therapy were more likely to complete the simulation. Subjects from the seven-session therapy also showed improvement in the claustrophobia scale, which lasted for at least three months after treatment completion. The study showed that a one-session therapy was of inferior efficacy compared to the sevensession therapy. The seven-session therapy group showed a high success rate with lasting benefits. A brief psychotherapy course may be a safe and effective alternative for individuals with MRI avoidance.
Keywords: claustrophobia; fear; enclosed spaces; anxiety; acceptance and commitment therapy